Analisis dan Mitigasi Risiko pada Supply Chain dengan Metode House of Risk (HOR): Studi Kasus PT. CDE - Setiyadi, Nanda; Ernawati, Dira; Dewi, Sinta (Universitas Batanghari Jambi, 2025)
PT CDE is a strategic company owned by a State-Owned Enterprise (BUMN) specializing in the production of key equipment for Indonesia's defense system, particularly for the maritime sector. The House of Risk (HOR) model is an approach inspired by the FMEA (Failure Mode and Error Analysis) method. Risk assessment in this method is carried out using a metric called the Risk Priority Number (RPN), which consists of three factors: the probability of occurrence and the severity of the possible impact. The results show that there are 20 risk events and 41 risk agents that constitute supply chain risks, along with recommendations for mitigating priority risk agents.